Democracy and the Political Rights of Former Prisoners in Indonesia: A Legal Perspective - Alfian Widyatama; Isharyanto Isharyanto; Adriana Grahani Firdausy (CV. Dyoqu Publishing and Management, 2025)
Background; Debate persists over whether former prisoners may stand in Indonesia’s local elections; Constitutional Court Decision No. 42/PUU-XIII/2015 reshapes the line between electoral integrity and rights protection. Aims; To unpack the Court’s reasoning and assess how it protects ex-prisoners’ political rights while maintaining the credibility of local democratic contests. Methods; Normative juridical study employing doctrinal analysis of the 1945 Constitution, pertinent statutes, and Decision No. 42/PUU-XIII/2015, read alongside scholarly commentary and case-based interpretation. Result; The Court positions political participation as a basic right that cannot be curtailed arbitrarily, yet allows narrowly tailored, proportionate limits to deter abuse and uphold ethical governance. The ruling refines candidacy criteria, improves legal certainty, and aligns practice with justice, proportionality, and inclusive democracy. Conclusion; By recognizing conditional eligibility for ex-prisoners, the Court advances democratic inclusion without diluting electoral standards, offering a pragmatic constitutional pathway for balancing rights and good governance in Indonesia’s local elections.